ANALYSIS OF FOOD PRODUCTION AND CONSUMPTION IN ISLAMIC BUSINESS ETHICS: A CASE STUDY OF BUSER INVESTIGASI - Indah Kurnianingsih; Wan Norhaniza Wan Hasan (Universitas Islam Darul 'ulum Lamongan, 2025)
This study aims to analyze Indonesia's food production methods that violate Islamic business ethics by using substances that are not fit for human consumption. Articles, journals, and research reports from social media and television are used as secondary data sources in this descriptive qualitative research. The focus of the research is on Islamic business ethics norms, particularly in food production. Data is collected through case observations reported by the media, such as investigations by the Buser SCTV team. The results show that many producers violate the principles of ethical production in Islam by using raw materials that are unfit for consumption, such as rotten tomatoes, excessive preservatives, and hazardous recycled plastics. These cases indicate poor practices that could harm consumers, both in terms of health and safety. Other examples include the production of tempeh with unsafe ingredients and the use of chemicals without proper labeling. The conclusion of this study is that many business players in Indonesia have deviated from the corridor of Islamic business ethics, neglecting principles of honesty and safety in production, which adversely affects consumers and society at large. The implementation of Islamic business ethics is crucial to safeguarding the welfare of consumers